Evaluation of the Implementation Program Uma Naroman Project for the Community in Bibileo Village, Sub-District Viqueque City, Viqueque Municipality in 2023 - Carolina da Cruz; Martinho Mendes Pereira; Mariano Pinto Amaral; Ana Maria do Rosario; Tomas Pereira; Moises Aparicio Pires (Jurnal Locus Penelitian dan Pengabdian, 2026)
The Uma Naroman ba Povu (UNP) program is a government initiative in Timor-Leste designed to provide decent and affordable housing for low-income families, addressing the fundamental need for adequate shelter as a basic human right. This study evaluated the implementation of the UNP program in Bibileo Village, Viqueque Municipality, in 2023. The research employed a qualitative descriptive method using data collection techniques, including direct observation, in-depth interviews, and literature review. Data analysis was conducted using the interactive model proposed by Miles and Huberman, which involved data collection, data reduction, data presentation, and conclusion verification. The findings revealed several significant and interconnected issues across five key dimensions: physical construction, occupant health, location, facilities, and accessibility. Specifically, many houses experienced poor construction quality, including damaged roofs, cracked foundations, and inadequate sanitation facilities. Health-related standards were not fully achieved due to limited waste disposal systems and insufficient access to clean water facilities. Geographically, many houses were located far from essential public services, such as schools and healthcare facilities, while basic amenities, including dining areas and electricity, were frequently unavailable. Furthermore, the implementation process was affected by weak supervision from the Ministry of State Administration and the Social Audit Unit, resulting in housing outcomes that did not fully meet expected standards. Community involvement in decision-making processes remained limited, creating opportunities for political influence and favoritism in beneficiary selection. This study highlights that improving the effectiveness of the UNP program requires stronger monitoring mechanisms, increased community participation, and stricter compliance with technical and health standards to ensure sustainable benefits for targeted beneficiaries.